Improvement of lab-scale production of microalgal carbohydrates for biofuel production - Jerez-Mogollón, Silvia-Juliana; Rueda-Quiñonez, Laura-Viviana; Alfonso-Velazco, Laura-Yulexi; Barajas-Solano, Andrés-Fernando; Barajas-Ferreira, Crisóstomo; Kafarov, Viatcheslav (CT&F - Ciencia, Tecnología y Futuro, 2012)
This work studied the improvement of biomass and carbohydrate (glucose and xylose) lab–scale productivity in Chlorella vulgaris UTEX 1803 through the use of the carbon/nitrogen ratio. In order to do so, mixotrophic cultures were made by the modification of initial concentration of CH3COONa (5, 10 and 20 mM) and NaNO3 (0.97, 1.94 and 2.94 mM). All treatments were maintained at 23 ± 1ºC, with light/dark cycles of 12h : 12h for 5 days. It was found that in addition to the carbon/nitrogen ratio, time also influences the concentration of biomass and carbohydrates. The treatment containing 10 mM acetate: 1.94 mM nitrate, reached a concentration of 0.79 g/L of biomass, 76.9 μg/mL of xylose and 73.7 μg/mL of glucose in the fifth day. However, the treatment containing 20 mM acetate: 0.97 mM nitrate produced 1.04 g/L of biomass, 78.9 μg/mL of xylose and 77.2 μg/mL of glucose in the third day, while in the same day the treatment containing 0 mM acetate: 2.94 mM nitrate, produced 0.55 g/L of biomass, 40.2 μg/mL of xylose and 31.3 μg/mL of glucose. The use of carbon/nitrogen ratios improved biomass productivity (from 0.55 to 1.04 g/L) as well as xylose (from 40.2 to 78.9 μg/mL) and glucose (from 31.3 to 77.2 μg/mL) concentration, representing an improvement of up to two times the production of both biomass and carbohydrates in only 3 days of culture.